2012
DOI: 10.1371/journal.pone.0035380
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Modes of Binding between Human Sweet Taste Receptor and Low-Molecular-Weight Sweet Compounds

Abstract: One of the most distinctive features of human sweet taste perception is its broad tuning to chemically diverse compounds ranging from low-molecular-weight sweeteners to sweet-tasting proteins. Many reports suggest that the human sweet taste receptor (hT1R2–hT1R3), a heteromeric complex composed of T1R2 and T1R3 subunits belonging to the class C G protein–coupled receptor family, has multiple binding sites for these sweeteners. However, it remains unclear how the same receptor recognizes such diverse structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
182
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(199 citation statements)
references
References 30 publications
14
182
1
2
Order By: Relevance
“…For example, gurmarin inhibits the effect of sucralose but effects of acesulfame-K and glycyrrhizin are totally insensitive to gurmarin . Since sucralose and acesulfame-K bind to a similar portion of the Venus flytrap of the sweet taste receptor (Masuda et al 2012), the mechanism underlying the preferential effects of gurmarin . In this regard, gurmarin acts as a biased antagonist for T1R3 in many respects and attenuates a limited signaling cascade evoked by a limited number of agonists.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gurmarin inhibits the effect of sucralose but effects of acesulfame-K and glycyrrhizin are totally insensitive to gurmarin . Since sucralose and acesulfame-K bind to a similar portion of the Venus flytrap of the sweet taste receptor (Masuda et al 2012), the mechanism underlying the preferential effects of gurmarin . In this regard, gurmarin acts as a biased antagonist for T1R3 in many respects and attenuates a limited signaling cascade evoked by a limited number of agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular Modeling-Based on the sequence alignment reported by previous studies (13,18,39), homology models of human/mouse T1Rs and their chimeras were constructed by residue replacement using the Modeler (40) as templates of metabotropic glutamate receptors (9,10,41). Structure of GA I, lactisole, and glucuronic acid were obtained from ZINC version12 (42).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on chimera and mutation of the sweet taste receptor revealed multiple binding sites for its ligands. For example, artificial sweeteners aspartame and neotame and other low molecular weight sweet compounds interact with the binding site formed by the bottom of lobe 1 and the top of lobe 2 of ATD in hT1R2 (12,13). The taste-modifying protein neoculin binds the ATD of hT1R3 (14).…”
mentioning
confidence: 99%
“…In addition, biophysical experiments on the class C sweet receptor, consisting of the TAS1R2/TAS1R3 heterodimer, indicate that sucrose and glucose bind to the VFD of both the TAS1R2 and TAS1R3 subunits (5,6), whereas other sweeteners, such as aspartame and stevioside (Stev), interact only with the VFD2 (VFD of TAS1R2) subunit (7)(8)(9). Moreover, the allosteric binding site at the TMD3 (TMD of TAS1R3) interacts with modulators of the receptor function, such as lactisole (9, 10).…”
mentioning
confidence: 99%